STRATEGI DAN PENDEKATAN GURU PENDIDIKAN AGAMA ISLAM DALAM PEMBINAAN KEBERAGAMAAN REMAJA - Arni Zulianingsih (TA'DIBUNA: Jurnal Pendidikan Agama Islam, 2019)
The Strategy and Approach of Teachers of Islamic Education in Youth Religious Development is qualitative research that aims to describe the phenomenon and context in implementing religious formation. This research is a case study because the focus of this study answers the question of "how-to" religious development and wants to cover contextual conditions that are relevant to the phenomenon. The results of this study indicate that the strategies in youth religious development here are divided into three, namely planning, implementation, and evaluation. Whereas the approach in religious development uses a contextual approach, including planning and learning processes carried out in accordance with contextual steps. And in adolescent diversity, there are several patterns of religious formation, including a. Coaching carried out by Islamic Education teachers, and b. Religious development by schools and teachers in addition to Islamic Education. The conclusion of the strategy and approach of the teacher of Islamic Education has a positive and significant influence on the religious development of adolescents.Keywords: Strategy, Approach, Diversity Development.